2005
DOI: 10.1111/j.1467-842x.2005.tb00748.x
|View full text |Cite
|
Sign up to set email alerts
|

National serosurvey of poliovirus immunity in Australia, 1996–99

Abstract: This is the first national serosurvey for immunity to poliovirus in Australia. Herd immunity is probably sufficient to prevent generalised outbreaks due to type 1 and 2 poliovirus, but this may not be the case for type 3. However, localised outbreaks of any poliovirus type could still occur following reintroduction unless uniformly high levels of vaccination coverage are maintained. Ongoing serosurveillance is required following the recent change back to inactivated polio vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…36,37 Of special note, a study in Australia based on over 1800 blood samples demonstrated male dominant seropositivity of poliovirus in younger age groups; an opposite trend was seen in the adult age groups. 38 This result is interesting especially as the injection of inactivated polio vaccine in 2000 children resulted in non-gender-specific seroconversion. 39 As our current study was not designed or powered to explain the genderspecific prevalence of HTLV-1 and other viruses, further studies are required to link the findings in different viruses and conditions.…”
Section: Potential Mechanism Of Paradoxical Male Predominance Of Htlvmentioning
confidence: 93%
See 1 more Smart Citation
“…36,37 Of special note, a study in Australia based on over 1800 blood samples demonstrated male dominant seropositivity of poliovirus in younger age groups; an opposite trend was seen in the adult age groups. 38 This result is interesting especially as the injection of inactivated polio vaccine in 2000 children resulted in non-gender-specific seroconversion. 39 As our current study was not designed or powered to explain the genderspecific prevalence of HTLV-1 and other viruses, further studies are required to link the findings in different viruses and conditions.…”
Section: Potential Mechanism Of Paradoxical Male Predominance Of Htlvmentioning
confidence: 93%
“…The study period was chosen because only immunofluorescence was used before 1995, and more recent samples were not included to avoid the bias of the exclusive bottle-feeding campaign for HTLV-1 carrier mothers that began in the late 1980s. 8 The seroprevalence of HTLV-1 was analyzed using binary logistic models respectively over five age bands of G [16][17][18][19] (16 ≤ age at donation < 20 years old), G 20-29 (20 ≤ < 30), G [30][31][32][33][34][35][36][37][38][39] (30 ≤ < 40), G [40][41][42][43][44][45][46][47][48][49] (40 ≤ < 50) and G 50-64 (50 ≤ < 65) with gender and study epochs (year at donation: 1995, 1996, 1997 and 1998) as independent variables. The age at donation was not included within the model because the seroprevalence in each age band within our study is not likely to reflect the natural age-related change because of potential biases (see Section 5 for detail).…”
Section: Methodsmentioning
confidence: 99%
“…Live attenuated (oral) polio vaccine was the predominant vaccine used during the study period; it was removed from the Australian immunisation schedule in November 2005 [22]. Two indicators of the population prevalence of immunity were available: estimates from a national serosurvey based on sera collected between 1996 and 1999 [23], and data from the Australian Childhood Immunisation Register (ACIR) [24] which are considered to give a minimum estimate of vaccination coverage due to delayed notification and vaccination [25,26]. Serosurvey data are considered to provide a better indicator of the proportion of the population who are susceptible to poliovirus infection, as immune status is also influenced by naturally acquired immunity and waning immunity [27].…”
Section: Methodsmentioning
confidence: 99%
“…According to Gidding (2005), only 2% of 10-19 year-old Australians in the community had not been exposed to any polio vaccine.…”
Section: Self-reported Health Statusmentioning
confidence: 99%